Ineffectiveness of the action of repetition in the municipality of Florencia, Caquetá. Case study, 2010-2016 - Bustos Ortega, Juan Sebastián; Rosas Sánchez, Carlos Javier (DIXI, 2019)
Purpose: The purpose of this paper is to establish the effectiveness of the action of repetition, and thus to determine the impact of the means of control on the recovery of money invested for the payment of judicial sentences in the municipality of Florencia, Caquetá, in the period 2010-2016.Methodology: In order to achieve this objective, a basic research was proposed, with a descriptive study and a deductive research method. It will consult statistical sources and use the systematization of data for its analysis as an information collection technique.Findings: Extra-contractual civil liability is one of the guarantees inherent to modern states, with which it is sought to provide society with mechanisms to exercise the payment of compensation on the conduct of public officials. Therefore, actions or means of control were implemented in our regulations as procedural mechanisms to request compensation for damages.Conclusions: in the municipality of Florencia, Caquetá, the effectiveness of the action of repetition in the 2010-2016 period is null. The City Hall has only initiated three actions of which only one was filed of 89 convictions against the municipality.
Keywords: Action of repetition; Florencia’s City Hall; Caquetá; extra-contractual civil liability; judicial sentences